2014
DOI: 10.1002/adfm.201401642
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Cancer Cell Migration by Gold Nanorods: Molecular Mechanisms and Implications for Cancer Therapy

Abstract: Gold nanorods have received much attention because of their distinct physicochemical properties and promising applications in bioimaging, biosensing, drug delivery, photothermal therapy, and optoelectronic devices. However, little is known regarding their effect on tumor metastasis. In the present investigation, serum protein‐coated gold nanorods (AuNRs) at low concentrations is shown to exhibit no apparent effects on the viability and proliferation of three different metastatic cancer cell lines, that is, MDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
83
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(87 citation statements)
references
References 54 publications
1
83
3
Order By: Relevance
“…Herein, we reported that targeting AuNRs to cancer cell surface integrins could greatly rearrange the cytoskeleton proteins, thus enhancing the inhibition effect on cancer cell migration. Compared with nontargeted AuNRs, the integrin-targeted AuNRs are more effective on cell migration inhibition with a nanoparticle concentration at the nM scale (1,000× lower than the literature values) (18,19,22), which could be safer for future clinical use.…”
Section: Integrinmentioning
confidence: 86%
See 3 more Smart Citations
“…Herein, we reported that targeting AuNRs to cancer cell surface integrins could greatly rearrange the cytoskeleton proteins, thus enhancing the inhibition effect on cancer cell migration. Compared with nontargeted AuNRs, the integrin-targeted AuNRs are more effective on cell migration inhibition with a nanoparticle concentration at the nM scale (1,000× lower than the literature values) (18,19,22), which could be safer for future clinical use.…”
Section: Integrinmentioning
confidence: 86%
“…Due to their small size and surface modifications, nanoparticles, in general, are able to target tumors selectively (15) and have been widely used in cancer diagnosis and therapy (16,17). The recent discovery of nanoparticles' effect on inhibiting cancer cell migration or metastasis starts to draw the attention of researchers (18)(19)(20)(21)(22). However, high concentrations of nontargeted nanoparticles (in μM) were used in these previous studies, which might be an obstacle when considering the translation to clinical use.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[23][24][25] The second novelty was the optimization of AuNRs-PPTT's conditions to generate tumor apoptosis as a favorable cell death mechanism (rather than necrosis). 12,26,27 Herein, we directly injected the PEGylated AuNRs to the mammary tumors of each canine/feline as opposed to intravenous injection, as our previous study showed a better efficacy for intratumoral injection than intravenous injection, 1 although the latter could be helpful for some applications (especially for tumors that are not accessible for direct injection of AuNR). 8 We tested PPTT on canine and feline natural mammary gland tumors.…”
Section: Introductionmentioning
confidence: 99%